The role of oil in the modernization of the Sultanate of Oman through the Five-Year Plan 1996-2000 - Al-Maliki, Ali Jowda Subayh Abbas (Journal of Humanities & Social Sciences, 2021)
The Sultanate of Oman was able to achieve by the oil sector and impact on the rest of the other sectors، where increased government spending in the field of education، health، services and infrastructure development، despite this development in the Sultanate of Oman through the oil sector so it must be looking for other sources to stimulate development because the oil sector sector Depleted، and there are surpluses of oil money with multiple dimensions and the effects of overlapping and mutual، The use of oil surpluses in modernizing the Omani economy، especially in economic development through the formation of the banking institutions of the Organization of Petroleum Exporting Countries. The oil affects the banking markets and international investment markets and the growth of financial expertise associated with them in general with regard to the ability of countries of the third and fourth world to bargain and address the economic and political power of the more developed countries. The aim of this study is to focus on oil and a course in modernizing the Sultanate of Oman during the period of the five-year plan 1996-2000. The study concluded that the Omani economy is characterized by dynamism and keeping abreast of the global economic developments and is in line with the rapid international changes، which will achieve more planned and planned integration between the Omani economy and the global economy.